Development of the Leading Stock Markets and the Challenges to "BSE – Sofia" AD - Georgiev, Lyubomir; Naydenova, Krasimira (Research Papers, 2020)
Stock exchange trading does not exist in its classical form. Technological innovations implemented by electronic trading platforms and OTC markets offer additional opportunities to investors and attract them, changing bourses. Opportunities for greater access to the investment process create modern trends "financialisation", "demutualization", "hybridization", "automation", "consolidation" and impose transparency.The Bulgarian stock market remains unchanged from the mainstream trends in securities trading. It is created administratively and the state continues to be a majority shareholder both in the market operator and in the depository institution. The low market liquidity, the high ownership concentration and the lack of basic infrastructure units make the market unattractive, which is why it lags behind world developments.
Keywords: Stock exchange industry; Market fragmentation; Alternative trading systems; Demutualization; Consolidation; Market liquidity; Bulgarian stock exchange; Transparency; Stock market